THE SEISMIC CHARACTERISTICS OF NORTHERN PART OF KULONPROGO - Bambang Ruwantro; Yosaphat Sumardi; Denny Darmawan (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2016)
Microtremor signal measurements had been conducted in the northern part of Kulonprogro to obtain the seismic characteristics in the form of: the predominant frequency value, ampliﬁ cation factor, sediment thickness, seismic vulnerability index, the maximum ground vibration acceleration, and the ground shear strain value. The measurement was conducted at 18 points within geographical coordinates of 110.10° E-110.27° E and 7.64° S-7.80° S. The signals were analyzed using Horizontal to Vertical Spectral Ratio (HVSR) method. The results show that the predominant frequency value is in the range of 2.98-13.53 Hz; ampliﬁ cation factor is in the range of 1.6-10.1; sediment thickness is in the range of 5-60 m; seismic vulnerability index is in the range of 0.6 × 10 -6-5.8 × 10 -6 s /cm; maximum ground acceleration is in the range of 24-54 gal and ground shear strain value is in the range of 0.6 × 10 -4 – 4.4 × 10 -4.